109k views
1 vote
What is the simplest form of this expression w^2(-4w^2-2)+(-5w^2)(-2w^2-2)

User Rivi
by
5.1k points

2 Answers

5 votes
6w4+8w2
step-by-step.w2(4w2−2)+(5w2)(2w2−2)Distribute:=(w2)(4w2)+(w2)(−2)+(5w2)(2w2)+(5w2)(−2)=4w4+2w2+10w4+10w2Combine Like Terms:=4w4+2w2+10w4+10w2=(4w4+10w4)+(2w2+10w2)=6w4+8w2 answer
User Vyacheslav
by
5.8k points
7 votes
Answer:
6w⁴ + 8w²

Step-by-step explanation:
Before we begin, remember the following:
xᵃ * xᵇ = x⁺ᵇ
+ve * -ve = -ve
-ve * -ve = +ve
+ve * +ve = +ve

To solve this problem, we will follow the following steps:
1- get rid of the brackets using the distributive property
2- combine like terms

This can be shown as follows:
w²(-4w² - 2) + (-5w²)(-2w² - 2)
w²(-4w²) + w²(-2) + (-5w²)(-2w²) + (-5w²)(-2)
-4w⁴ - 2w² + 10w⁴ + 10w²
w⁴(-4+10) + w²(-2+10)
6w⁴ + 8w²

Hope this helps :)

User Lin Ma
by
5.0k points